Membership expansion of medical mission group hospital and health service cooperative of Oriental Mindoro converting patients to patient-members - Umali-Marquez, Glenda
A cooperative has a potential as an economic enterprise. It can also be a way to uplift the marginalized Filipino through pooling of their resources and using them for their own betterment. A group of doctors in Oriental Mindoro come together to emulate the Medical Mission Group Cooperative in Davao whose mission is to have a truly acceptable, accessible, affordable and sustainable health care delivery system to all people through their collective effort so that in the end no one shall have been left unserved. Membership expansion by opening it to clients and the community can answer many issues in the MMGHHSCOM but it is met with resistance by the General Assembly. This study aims to determine the factors affecting the recruitment of MMGHSCOM patients to patient-members. It specifically aims to described the socio-demographic profile of MMG patients who are willing/not willing to join and invest in MMGHHHSCOM; describe the reason for the choice of MMG Hospital among patients; determine the willingness of MMG patients to pay the required membership fee and share capital; determine patient satisfaction on MMGHHSCOM services and its influence on membership recruitment; describe the present image of the MMGHHSCOM among patients and its influence on decision to be a member; determine the acceptability of cooperative principles to the respondents; determine the acceptability offinancial returns the cooperative way; determine the acceptability of member benefits through discounts. Three hundred respondents who were admitted from September 15, 2010 to January 15, 2011 were included in the quantitative analysis and seven interviewees for focus group discussion. Results show that patients are willing to patronize MMG but not all are willing to invest. Factors such as cooperative principles, hospital image, financial benefits, member benefits and patient satisfaction to the services are acceptable to patients but not enough reason to sign up as members. The main determinant of clients? willingness to invest at the MMGHHSCOM is their financial capability. Patients of MMG come from low to middle income group and with the poverty line set at 12400, these patients barely have enough peso to spare after food and daily living allowance with the added stress on their finances because of a sick member of the family requiring hospitalization. The required number of share capital and membership fee is financially difficult for them to meet. Cooperative membership is cooperative ownership. The challenge for the management is to create an ownership culture. The management should concentrate their recruitment efforts on the healthy members of society who are potential clients in the end and starting this with co-coop members would be a much easier task. The owners and directors, staff and management and potential member-patients, should all understand that this economic model offers us many advantages, including the ability to serve members, build equity, and share in the common wealth.
Management Study (MHA)--University of the Philippines Manila, 2011
Keywords: Cooperatives